(untitled) (Physical Education, Health and Social Sciences, 2025)
Diabetic Nephropathy shows the predominant cause of renal failure in diabetics. It is also a significant contributor to clinical mortality which is characterized by the progressive decrement in renal morphology and physiology because of sustained hyperglycemia. As the disease progress, many patients ultimately require renal replacement therapy for end stage renal disease (ERSD). For this reason, early diagnosis and prompt interventions are crucial to limit disease progression, enhance clinical outcomes and conserve quality of life. The recognition of biomarkers for the early detection of DN is of predominant importance. In recent years, the process of recognition of novel biomarkers which offers valuable insights into the onset and progression of DN has been significantly increased. This review gives a comprehensive evaluation of emerging biomarkers associated with diabetic nephropathy.